Interacting straight-sided buckles: An enhanced attraction by substrate elasticity. (March 2019) - Coupeau, C.; Boijoux, R.; Ni, Y.; Parry, G.
Abstract: Interaction between two straight-sided buckles propagating in opposite directions has been investigated by atomic force microscopy. Below a critical separation distance, it is observed that the two buckles are attracted towards each other once their fronts have crossed. A mechanical analysis using finite element simulations has shown that the buckle interaction is strongly influenced by the substrate elasticity. The deviation of the two buckles from their initial straight propagation is discussed at the light of mode mixity mappings extracted from finite elements simulations along the crack path of the two interacting buckles. Finally, a phase diagram depending on both the separation distance and the film/substrate elastic mismatch is proposed, in good agreement with the experimental results. Graphical abstract: Image, graphical abstract